Renin-Angiotensin System and Sympathetic Neurotransmitter Release in the Central Nervous System of Hypertension - Kazushi Tsuda (International Journal of Hypertension)
Many Studies suggest that changes in sympathetic nerve activity in the central nervous system might have a crucial role in blood pressure control. The present paper discusses evidence in support of the concept that the brain renin-angiotensin system (RAS) might be linked to sympathetic nerve activity in hypertension. The amount of neurotransmitter release from sympathetic nerve endings can be regulated by presynaptic receptors located on nerve terminals. It has been proposed that alterations in sympathetic nervous activity in the central nervous system of hypertension might be partially due to abnormalities in presynaptic modulation of neurotransmitter release. Recent evidence indicates that all components of the RAS have been identified in the brain. It has been proposed that the brain RAS may actively participate in the modulation of neurotransmitter release and influence the central sympathetic outflow to the periphery. This paper summarizes the results of studies to evaluate the possible relationship between the brain RAS and sympathetic neurotransmitter release in the central nervous system of hypertension.